The Growth Characteristics of Patients with Noonan Syndrome: Results of Three Years of Growth Hormone Treatment: A Nationwide Multicenter Study - DEMİRCİOĞLU, SERAP (GALENOS YAYINCILIK, 2016)
Objective: Noonan syndrome (NS) is a multisystem disorder, and short stature is its most striking manifestation. Optimal growth hormone (GH) treatment for NS is still controversial. In this study, using a nationwide registration system, we aimed to evaluate the growth characteristics and the clinical features of NS patients in Turkey and their growth response to GH treatment. Methods: Children and adolescents with a diagnosis of NS were included inthe study. Laboratory assessment including standard GH stimulation test results were evaluated. Height increment of patients with or without GH treatment were analyzed after three years of therapy. Results: A total of 124 NS patients from different centers were entered in the web-based system. Short stature and typical face appearance were the most frequently encountered diagnostic features of our patients. Of the 84 patients who were followed long-term, 47 hadreceived recombinant human GH (rhGH). In this group of 47 patients, height standard deviation score (HSDS) increased from -3.62 +/- 1.14 to -2.85 +/- 0.96 after three years of therapy, indicating significant differences from the patients who did not receive GH treatment. PTPN11 gene was analyzed in 61 patients, and 64% of these patients were found to have a mutation. HSDS at admission was similar in patients with or without PTPN11 gene mutation. Conclusion: A diagnosis of NS should be kept in mind in all patients with short stature showing systemic clinical findings. GH therapy is effective for improvement of short stature especially in the first two years of treatment. Further studies are needed for optimisation of GH therapy and evaluation of final height data in NS patients.
Keywords: Noonan syndrome; growth hormone treatment; growth; CLINICAL-FEATURES; CHILDREN; THERAPY; HEIGHT; MUTATIONS; DIAGNOSIS